AtRsmD Is Required for Chloroplast Development and Chloroplast Function in Arabidopsis thaliana - Wang, Zi-Yuan; Qu, Wan-Tong; Mei, Tong; Zhang, Nan; Yang, Nai-Ying; Xu, Xiao-Feng; Xiong, Hai-Bo; Yang, Zhong-Nan; Yu, Qing-Bo (Frontiers in Plant Science, 2022)
AtRsmD was recently demonstrated to be a chloroplast 16S rRNA methyltransferase (MTase) for the m2G915 modification in Arabidopsis. Here, its function of AtRsmD for chloroplast development and photosynthesis was further analyzed. The AtRsmD gene is highly expressed in green photosynthetic tissues. AtRsmD is associated with the thylakoid in chloroplasts. The atrsmd-2 mutant exhibited impaired photosynthetic efficiency in emerging leaves under normal growth conditions. A few thylakoid lamellas could be observed in the chloroplast from the atrsmd-2 mutant, and these thylakoids were loosely organized. Knockout of the AtRsmD gene had minor effects on chloroplast ribosome biogenesis and RNA loading on chloroplast ribosomes, but it reduced the amounts of chloroplast-encoded photosynthesis-related proteins in the emerging leaves, for example, D1, D2, CP43, and CP47, which reduced the accumulation of the photosynthetic complex. Nevertheless, knockout of the AtRsmD gene did not cause a general reduction in chloroplast-encoded proteins in Arabidopsis grown under normal growth conditions. Additionally, the atrsmd-2 mutant exhibited more sensitivity to lincomycin, which specifically inhibits the elongation of nascent polypeptide chains. Cold stress exacerbated the effect on chloroplast ribosome biogenesis in the atrsmd-2 mutant. All these data suggest that the AtRsmD protein plays distinct regulatory roles in chloroplast translation, which is required for chloroplast development and chloroplast function.